2017
DOI: 10.20900/jpbs.20170018
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Intervention in Animal Models of Autism

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopment disorder caused by genetic and environmental factors. Animal models of autism could help to explore the cellular and molecular mechanisms underlying the pathogenesis and treatment approaches of this disease. Environmental enrichment has been demonstrated to exert beneficial effects in wild-type rodents as well as animal models of various neurological and psychiatric disorders. Here we review the findings about the effect of environmental enrichment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Research using animal models of autism has focused mainly on the genetic mechanisms underlying this disorder. Several studies investigated home-cage enrichment as an environmental modifier, which has been shown to ameliorate the autism-like phenotype in some genetic models [28][29][30] . However, sex is also a modifier of autism risk.…”
Section: Introductionmentioning
confidence: 99%
“…Research using animal models of autism has focused mainly on the genetic mechanisms underlying this disorder. Several studies investigated home-cage enrichment as an environmental modifier, which has been shown to ameliorate the autism-like phenotype in some genetic models [28][29][30] . However, sex is also a modifier of autism risk.…”
Section: Introductionmentioning
confidence: 99%